2021
DOI: 10.1001/jamanetworkopen.2021.1809
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival Outcomes Among Patients With Breast Cancer With Distant vs Ipsilateral Supraclavicular Lymph Node Metastases

Abstract: IMPORTANCE There is a lack of studies exploring whether the survival of patients with distant lymph node metastases (DLNM) is different from that of patients with ipsilateral supraclavicular lymph node metastases (ISLM) and other stage IV breast cancer. OBJECTIVE To assess the survival of patients with DLNM from breast cancer vs ISLM and other stage IV breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Our data demonstrated that in multimodal therapy, SND in addition to systemic therapy was associated with overall survival improvement when compared with no surgery, and the results are consistent with recent studies showing that long-term survival outcomes of patients with sSLNM were improved by multimodal therapy with curative intent [ 22 , 23 ]. As intensive clinical surveillance with modern imaging modalities, such as sonography, to detect subclinical distant nodal relapse earlier and multimodal therapy, including SND and systemic therapy, were associated with improved 5-year DMFS, RFS, and OS, we can treat miSLNM as locoregional relapse rather than systemic metastasis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data demonstrated that in multimodal therapy, SND in addition to systemic therapy was associated with overall survival improvement when compared with no surgery, and the results are consistent with recent studies showing that long-term survival outcomes of patients with sSLNM were improved by multimodal therapy with curative intent [ 22 , 23 ]. As intensive clinical surveillance with modern imaging modalities, such as sonography, to detect subclinical distant nodal relapse earlier and multimodal therapy, including SND and systemic therapy, were associated with improved 5-year DMFS, RFS, and OS, we can treat miSLNM as locoregional relapse rather than systemic metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, miSLNM and contralateral axillary lymph node metastasis (CAM) are staged as rN3c or M1 disease (in our series, most of the locations of metastatic nodes were beyond the triangle of supraclavicular fossa and involved the level III and IV and even level V of neck), while many studies have demonstrated that both miSLNM and CAM are associated with a better prognosis than distant metastasis if managed with intensive multimodal therapy with curative intent [ 18 , 20 , 22 , 25 ]. Surgical removal of miSLNM is usually neglected in multimodal therapy because it is categorized as systemic disease with inconsistent survival benefit of surgical treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Lymph nodes are the central transport center of circulating immune cells, with the lymphatic drainage system of the body a coherent whole separated by particular anatomical boundaries (10)(11)(12). Patients with extra-regional lymph node metastasis are considered to have better prognosis than those with solid organ metastasis among some metastatic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with extra-regional lymph node metastasis are considered to have better prognosis than those with solid organ metastasis among some metastatic malignancies. The research by Hong Pan showed that patients with distant lymph node metastasis (DLNM) had similar breast cancer-specific survival (BCSS) and OS as those with ipsilateral supraclavicular lymph node metastasis (ISLM), whereas those with distant metastasis (not DLNM) had significantly poorer BCSS and OS (12). Similarly, Francesca Magnoni found that although contralateral axillary lymph node metastasis after treatment belongs to distant metastasis (distant lymph node metastasis), its OS is significantly better than the distant metastasis of other organs (13).…”
Section: Discussionmentioning
confidence: 99%
“…The patients with distant lymph node metastasis were once considered as surgical contraindication [3]. But according to Hong Pan et al [4], patients with distant lymph node metastases (DLNM) had similar breast cancer-speci c survival (BCSS) and overall survival (OS) with patients with ipsilateral supraclavicular lymph node metastases (ISLM) and locoregional therapies were signi cantly associated with improved overall survival for patients with DLNM. We herein present a case of breast cancer with contralateral neck lymph node metastasis of a 30-year-old woman, exhibit its clinical, morphological, pathological and immunohistochemical characteristics and discuss its treatment combined with current research.…”
Section: Introductionmentioning
confidence: 99%